2019
DOI: 10.1371/journal.pone.0210316
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia, subclinical inflammation, hepatic cholestasis and endothelial dysfunction in schoolchildren with excess fat: A study from the United Arab Emirates

Abstract: BackgroundThe impact of obesity on cardiovascular health of young children is still to be fully illustrated. This study measured biomarkers for glycemic control, lipid metabolism, systemic inflammation, endothelial dysfunction, and hepatic cholestasis in schoolchildren. Its main purpose was to determine whether metabolic derangements could be detected in young children with excess fat.MethodThis cross-sectional study involved 967 children in the second, sixth, and tenth grades (median age, 7.3, 11.3, and 15.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
3
3
0
Order By: Relevance
“…In this study, hsCRP was significantly higher in children with overweight or obesity whereas IL6 levels showed no differences between groups. Our results regarding hsCRP agree with several previous studies in which it has been associated in children with overweight and obesity in different populations [47][48][49]. In this study, leptin levels were significantly increased in children with overweight and obesity, as has consistently been observed in previous studies [50][51][52].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, hsCRP was significantly higher in children with overweight or obesity whereas IL6 levels showed no differences between groups. Our results regarding hsCRP agree with several previous studies in which it has been associated in children with overweight and obesity in different populations [47][48][49]. In this study, leptin levels were significantly increased in children with overweight and obesity, as has consistently been observed in previous studies [50][51][52].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, in our study, excess weight boys and girls had increased CVD risk factors such as higher TG, low HDL-C in boys, and elevated SBP in girls compared to normal-weight children. The relationship between excess body fat and CMRF has been reported in the literature, and researchers have explained that the chronic inflammatory process is caused by excess fat accumulated explicitly in the abdominal cavity [41][42][43]. In our previous report [43], we demonstrated that dyslipidemia was adversely associated with endothelial dysfunction in school-aged children and, through this research, we identified that excess weight children had concomitant lipid profile disorders and particularly increased TG levels at early ages.…”
Section: Discussionsupporting
confidence: 59%
“…The relationship between excess body fat and CMRF has been reported in the literature, and researchers have explained that the chronic inflammatory process is caused by excess fat accumulated explicitly in the abdominal cavity [41][42][43]. In our previous report [43], we demonstrated that dyslipidemia was adversely associated with endothelial dysfunction in school-aged children and, through this research, we identified that excess weight children had concomitant lipid profile disorders and particularly increased TG levels at early ages. Our study findings imply that abnormal weight gain must be identified early, the primary prevention of CVD in children be prioritized, and the risks for undesirable structural and metabolic changes must ultimately be reduced.…”
Section: Discussionsupporting
confidence: 59%
“…Nonetheless, as stated in the literature review, in addition to obesity, undernutrition also remains an issue. Studies in Saudi Arabia and Egypt reported several children to be undernourished and stunted [ 18 , 19 , 99 ]. Similarly, a study conducted in the UAE in 2013 reported that 7.6% of Emirati schoolchildren were underweight [ 21 ].…”
Section: Discussionmentioning
confidence: 99%